Competition on the Origins of Life and the Scientific Oratory Tradition: Polarizing Evolution and Its Instinctual Faith in Prometheus - Yergensen, Brent (New Explorations, 2023)
Predating the current billionaire space race, Ridley Scott’s Prometheus explores an interplay of competing explanations of the origins of life as discoverable in the universe through space exploration. The film’s plot debates evolution versus faith as life’s origins, and demonstrates evolution as victorious over and utilizing faith. Accompanying this analysis is focus on the film’s previously released online prologue scene, a fictional TED Talk that intertwines technological advancements and religious themes that display a brutal Darwinian survival of the fittest hierarchy as the answer to life’s origins. In the age of re- emerging space exploration, Prometheus and its social media-released prologue oration demonstrate technological control over evolution and relegate faith to functioning as a survival mechanism in response to superior and hyperaggressive species. Faith’s value is in assisting humanity to continually seek transcendent answers when confronting life’s beginnings and violent endings.